Partial purification and characterisation of Î±-amylases from the digestive tract of the Indian major carp Labeo rohita (Hamilton, 1822) - ., Umalatha; Sridhar, N.; Kushwaha, Jairam Prasad; Kumar, Vadlapudi (Indian Journal of Fisheries, 2020)
Partial purification of Î±-amylases from the digestive tract of the Indian major carp Labeo rohita (Hamilton, 1822) through acetone fractionation and ion exchange chromatography (DEAE-SephadexA-50) resulted in 8-fold purification with 86% recovery. Characterisation of amylase activity revealed two pH optima at 4.5 and 6.5. Activity was stable over wide pH ranges of 3.5 to 4.5 and 7 to 12. Optimum incubation temperature was 35Â°C. The enzyme lost 91% activity at 60Â°C within 15 min and was inhibited by Amylase inhibitor Type-1 (wheat); 1, 10 Phenanthroline, Ethylene diamine tetra-acetate (EDTA) and Phenyl methyl sulphonyl fluoride (PMSF). Heavy metal ions Hg++ and Cu++ strongly inhibited the enzyme activity, while Zn++ and Bi++ inhibited to a lesser extent. Native polyacrylamide gel electrophoresis of the purified amylase fractions revealed four bands, with corresponding molecular weights of 43.59, 52.36, 55.42 and 54.01 kDa. Î±-Amylase activity from L. rohita exhibited linear hydrolysis of starch upto 7% concentration in 60 min.Keywords: Î±-Amylase, ,Characterisation, Digestive tract, Labeorohita, Purification